Toward a Code of Ethics for Management Accountants (Book). - Meyer, Philip E.; Bruns, William J. (The Accounting Review, 1983)
Reviews the book "Toward a Code of Ethics for Management Accountants," by C. Mike Merz and David F. Geoebner.